Ultraviolet Index measurements in the Indian Ocean - Portafaix, Thierry; Lamy, Kevin (PANGAEA, 2021)
Within the framework of various programmes funded by Europe, Reunion Council or CNES (French Space Agency), the University of Réunion Island has developed a specialized network for the measurement of UV radiation and cloud cover in the south-western part of the Indian Ocean, known as the UV-Indien network. The western Indian Ocean is mainly located in the tropical region of the southern hemisphere. This part of the world is therefore potentially impacted by the changes in radiation described above. However, this geographical area suffers from a very large measurement deficit, both for ozone and UV radiation on the ground. The data-sets presented here are original and, as mentioned, concern an extremely poorly measured region of the globe, which highlights their importance. They include the UV index at 9 stations, the cloud fraction measured at 4 stations. These measurements are ideally suited for assessing the effect of UV radiation on the health of people or ecosystems in this region. This network currently has 9 stations in 5 countries of the Region (France, Madagascar, Seychelles, Comoros and Mauritius), with 8 scientific, institutional or meteorological partners. All stations are now equipped with a Kipp & Zonen UVS-E-T broadband radiometer. Reunion Island is also equipped with a Bentham UV spectroradiometer. The raw UV measurements obtained by the radiometers are reprocessed considering the calibrations and TOC measured simultaneously. The broadband radiometers will be calibrated every 2 years at the Moufia super site (University of Reunion Island, St Denis) using the Bentham UV spectrometer, itself calibrated every 3 months Cloud cover measurements are carried out using the wide-angle total sky imager, SkyCamVision (SCV), , manufactured by Reuniwatts (http://www.reuniwatt.com/). Cloud fractions (CF) are calculated following a cloud segmentation algorithm.
Keywords: clouds; Indian Ocean; radiation measurement; solar radiation; ultraviolet; UVI